Synthesis of a soluble flag-tagged single chain variable fragment (scFv) antibody targeting Cucumber Mosaic Virus (CMV) coat protein - Chua, K.H.; Seng, T.C.; Khalid, N.; Harikrishna, J.A.; Othman, R.Y. (Malaysian Society for Molecular Biology and Biotechnology, 2003)
Cucumber mosaic virus (CMV) is a serious pathogen of many economically important commercial fruit and vegetable crops worldwide. It is a particular problem in warmer climates, where plants are not grown under cover thus necessitating undesirably high use of agrochemicals for the control of insect vectors. Efforts towards controlling of this virus would include the development of improved methods of virus detection including the ability to produce cost effective and specific reagents. In this study the production of recombinant antibodies provides one such approach. A single chain variable fragment (scFv) antibody, targeted to CMV coat protein, was constructed with mRNA from the spleen of a CMV coat protein-immunized mouse. The nucleotide sequence of the variable heavy (VH) and variable light (VL) framework regions of the mouse spleen cDNA were used to design and construct primers for scFv library construction via RT-PCR. Three rounds of panning of the scFv library with the coat protein of a local isolate of a chilli strain CMV resulted in the cloning of a novel soluble Flag-tagged scFv antibody that suitable for use as a diagnostic reagent with the further potential of in situ application in the development of transgenic plants with novel resistance.